Novel biomarkers for early diagnosis of acute kidney injury after cardiac surgery in adults - Gavrić, Aleksandar; Kališnik, Jurij Matija (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
Acute kidney injury after cardiac surgery with cardiopulmonary bypass is a common and serious complication and it is associated with increased morbidity and mortality. Diagnosis of acute kidney injury is based on the serum creatinine levels which rise several hours to days after the initial injury. Thus, novel biomarkers that will enable faster diagnosis are needed in clinical practice. There are numerous urine and serum proteins that indicate kidney injury and are under extensive research. Despite promising basic research results and assembled data, which indicate superiority of some biomarkers to creatinine, we are still awaiting clinical application.